Pengaruh Tingkat Kualitas Pelayanan dalam Pengurusa Paspor terhadap Kepuasan Pemohon di Kantor Imigrasi Kelas II Non TPI Bima - Nur Hidayah; Djoko Widagdo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Service quality is a service that has a characteristic quality. Characteristics of good quality include ease, speed, accuracy, reliability and empathy from service officers in providing and delivering services to someone who has a strong impression that can be directly felt by customers at that time and at that time. This study uses a quantitative method. It can be concluded that the service quality variable (X) has a significant influence on applicant satisfaction (Y) at the Bima Immigration Office. The sig value (0.000) <0.05 is seen, which means that the quality of Passport services has an influence on the satisfaction of applicants at the Class II Non-TPI Bima Immigration Office.This study uses a quantitative method. The method used to obtain data and information in this study is by using a survey method using a questionnaire. The survey method used is by distributing questionnaires to applicants at the Class II Non-TPI Bima Immigration Office. The data analysis techniques used are validity test, reliability test, classical assumption test, significance test (t-test), and coefficient of determination test (R2 test).The discussion of the research aims to provide results and an overview of this research. According to the results of data analysis with simple linear regression, it shows that the variable X or service quality has an influence on the variable Y or passport applicant satisfaction with a significant value of service quality (X) on passport applicant satisfaction (Y) of 0.000 <0.05. In this study, the variable Service Quality (X1) has an influence on applicant satisfaction (Y), because if the quality of service (X) provided by the officer to the applicant is bad, it will cause dissatisfaction of passport user applicants, thereby reducing the applicant's loyalty in using services at Bima Immigration. And the value of the coefficient of determination or R square is 0.768, meaning that the service quality variable contributes 0.768 or 76.8% to passport applicant satisfaction.